2015
DOI: 10.1039/c4ra09883h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and click modification of an azido-functionalized Zr(iv) metal–organic framework and a catalytic study

Abstract: An azido-functionalized Zr(II) metal-organic framework (MOF), UiO-67-N 3 , was synthesized from 2-azidobiphenyl-4,4 0 -dicarboxylic acid. During the synthesis, the ligand can undergo in situ thermocyclization to give 9H-carbazole-2,7-dicarboxylic acid. It proved that UiO-67-N 3 can be obtained at relatively low temperature without ligand transformation. Post-synthetic modification of UiO-67-N 3 was successfully performed via the click reactions between the azido group and different alkyne compounds to produce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…UiO‐67‐N 3 , which contains 2‐azidobiphenyl‐4,4′‐dicarboxylate, has been prepared, although the reaction temperature had to be reduced to 80 °C as conventional synthetic methods (140 °C) resulted in thermal cyclisation of the ligand to 9 H ‐carbazole‐2,7‐dicarboxylate in situ . This phenomenon also results in a poor thermal stability of the MOF, as thermal cyclisation results in a bent ligand geometry that cannot be accommodated by the framework, resulting in collapse of the overall network structure.…”
Section: Pendant Covalent Functionalisationmentioning
confidence: 99%
“…UiO‐67‐N 3 , which contains 2‐azidobiphenyl‐4,4′‐dicarboxylate, has been prepared, although the reaction temperature had to be reduced to 80 °C as conventional synthetic methods (140 °C) resulted in thermal cyclisation of the ligand to 9 H ‐carbazole‐2,7‐dicarboxylate in situ . This phenomenon also results in a poor thermal stability of the MOF, as thermal cyclisation results in a bent ligand geometry that cannot be accommodated by the framework, resulting in collapse of the overall network structure.…”
Section: Pendant Covalent Functionalisationmentioning
confidence: 99%
“…This transformation of H 2 azideBPDC has recently also been reported in literature when high temperatures (> 80 °C) were used during the synthesis of the Zr-based framework UiO-67. 58 The formation of the carbazole led to a slightly bent linker molecule and therefore a changed geometry, which might be the reason for the low crystallinity of the azide-containing MOFs. Nitrogen physisorption measurements were performed to determine the accessible pore volumes and specific surface areas.…”
Section: Characterizationmentioning
confidence: 99%
“…[36][37][38][39][40][41] Click chemistry, [42][43][44] which can proceed the reaction efficiently with high yields and high specificity in the presence of various functional groups, has received a great deal of use in different fields, for example, dendrimer synthesis [45,46] and surface science. More recently, Gao et al [57] reported another azide-MOF, which was subjected to PSM with different alkynes through click reaction and the resulting MOFs can be used as catalysts for Knoevenagel condensation reactions. [50][51][52][53][54][55] In this review, we will summarize the research progress of PSM of MOFs through click chemistry.…”
Section: Introductionmentioning
confidence: 99%